Treatment of Landfill Leachate Using Activated Sludge Technology: A Review. (4th September 2018) - Wang, Kai; Li, Lusheng; Tan, Fengxun; Wu, Daoji
Abstract : Landfill leachate contains a large amount of organic matter and ammoniacal nitrogen. As such, it has become a complex and difficult issue within the water treatment industry. The activated sludge process has been found to be a good solution with low processing costs and is now therefore the core process for leachate treatment, especially for nitrogen removal. This paper describes the characteristics and treatment of leachate. Treatment of leachate using the activated sludge process includes the removal of organic matter, ammoniacal nitrogen, and total nitrogen (TN). The core method for the removal of organic matter involves anaerobic treatment supplemented with an aerobic process. Ammoniacal nitrogen is commonly removed using a conventional aerobic treatment, and advanced TN removal is achieved using endogenous denitrification or an anaerobic ammonium oxidation (ANAMMOX) process. Since biological processes are the most economical method for TN removal, a key issue is how to tap the full potential of the activated sludge process and improve TN removal from leachate. This complex issue has been identified as the focus of current scholars, as well as an important future direction for leachate research and development.